2015
DOI: 10.2494/photopolymer.28.293
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Microbubbles on Ozonized Water for Photoresist Removal

Abstract: The existence of microbubbles in ozonized water has been shown to significantly enhance the photoresist removal rate due to an elevated dissolved ozone concentration and a direct effect of the microbubbles relating to the radical generation. Additionally, the ozone microbubble solution was able to effectively remove a high-dose ion-implanted photoresist, which is extremely resistant to removal by ozonized water and other wet chemicals because of its amorphous carbon-like layer, or "crust". Electron spin resona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 17 publications
1
13
0
Order By: Relevance
“…As demonstrated in our earlier work [15,16], which are produced together with H and O radicals [18]. According to some findings [19][20][21][22][23], OH radicals actually have higher reactivity to benzene rings than either H or O radicals. The decrease over 1.5% might be attributable to the decreased production rate of H radicals by the catalytic poisoning of the catalyst surface by O atoms.…”
Section: Resultsmentioning
confidence: 74%
“…As demonstrated in our earlier work [15,16], which are produced together with H and O radicals [18]. According to some findings [19][20][21][22][23], OH radicals actually have higher reactivity to benzene rings than either H or O radicals. The decrease over 1.5% might be attributable to the decreased production rate of H radicals by the catalytic poisoning of the catalyst surface by O atoms.…”
Section: Resultsmentioning
confidence: 74%
“…In contrast to traditional ozone bubble, the COD removal efficiency was higher by 20% and the time required for 80% removal of colour was less by 140 min in the MBs system. More studies [66–72] showed that the synergistic effects of the MNBT and ozone/UV could give full play to their advantages to effectively enhance the decomposition of organics, the biodegradability and the effect of decolourisation.…”
Section: Sewage (Waste) Water Treatmentmentioning
confidence: 99%
“…Next, his group reported that the ∙OH producing in both cases of air (oxygen microbubbles and nitrogen microbubbles) in the acidic condition at pH 2 and 3 2 and the generation of hydroxyl radicals from the collapse of oxygen or air microbubbles was markedly enhanced by the existence of copper ion catalyst by the copper wire under pH2.2 acidic HCl solution 3 . Also, the microbubbles on ozonized water indicated the presence of hydroxyl radical by the collapse of microbubble 4 . Recent papers are referred the above papers 5 and the oxygen nanobubble stability was confirmed to be pH-dependent and the collapsed oxygen nanobubble generate the free radical that induced the photodegradation of oxytetracycline 6 .…”
Section: Introductionmentioning
confidence: 97%